Forgetting in early modern English literature and culture : Lethe's legacies - Ivic, Christopher, 1968-; Williams, Grant, 1965- (Routledge studies in Renaissance literature and culture., 2004)
Opening up an area overlooked by Renaissance scholarship, this collection of essays historicizes and theorizes 'forgetting' in English literary texts.